2020
DOI: 10.1038/s41598-020-70894-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of strong candidate genes for backfat and intramuscular fatty acid composition in three crosses based on the Iberian pig

Abstract: Meat quality has an important genetic component and can be modified by the fatty acid (FA) composition and the amount of fat contained in adipose tissue and muscle. The present study aimed to find genomic regions associated with the FA composition in backfat and muscle (longissimus dorsi) in 439 pigs with three different genetic backgrounds but having the Iberian breed in common. Genome-wide association studies (GWAS) were performed between 38,424 single-nucleotide polymorphisms (SNPs) covering the pig genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 119 publications
(185 reference statements)
3
38
0
Order By: Relevance
“…On the one hand, it is known as a fat type pig, producing fine quality meat as a delicacy with a considerably high proportion of intramuscular fat and a high amount of unsaturated fatty acids compared to other pig breeds 47 . In that respect, it was no surprise that we identified several genes in Mangalitza consensus ROHR, which were proposed to have an impact on fat metabolism including lipase I (LIPI) and phospholipase A2 group IID (PLA2G2D) influencing fatty acid composition of meat 48 , 49 or phospholipase A2 group V ( PLA2G5), hydroxysteroid 11-beta dehydrogenase 1 (HSD11B1) and diacylglycerol kinase delta (DGKD) , which have a crucial role in insulin resistance and the susceptibility for obesity 50 52 .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it is known as a fat type pig, producing fine quality meat as a delicacy with a considerably high proportion of intramuscular fat and a high amount of unsaturated fatty acids compared to other pig breeds 47 . In that respect, it was no surprise that we identified several genes in Mangalitza consensus ROHR, which were proposed to have an impact on fat metabolism including lipase I (LIPI) and phospholipase A2 group IID (PLA2G2D) influencing fatty acid composition of meat 48 , 49 or phospholipase A2 group V ( PLA2G5), hydroxysteroid 11-beta dehydrogenase 1 (HSD11B1) and diacylglycerol kinase delta (DGKD) , which have a crucial role in insulin resistance and the susceptibility for obesity 50 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a large number of quantitative trait loci (QTL) or candidate genes for IMF have been identified by linkage and genomewide association (GWA) studies. However, despite the progress achieved in this field in recent years, molecular mechanisms behind IMF trait remains elusive, as few causative genes or causative mutations affecting IMF content of pork have been determined (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…This result agreed with previous studies, which indicated that stearic acid had a positive phenotypic and genetic correlation with arachidic acid levels in the backfat tissue of pigs [ 49 , 50 ]. Moreover, numerous previous studies have proposed the elongation of long-chain fatty acid family number 7 ( ELOVL7) as a strong candidate gene that is indicative of the GWAS signals associated with arachidic acid levels and the metabolic indexes of arachidic to stearic acid or the ratios of eicosenoic to arachidic acid levels [ 9 , 10 , 51 , 52 ]. The evidence presented above indicates that the TNFRSF19 gene may have a relationship with arachidic acid levels and may be related to the genes that regulate FA metabolism in muscle tissues.…”
Section: Discussionmentioning
confidence: 99%